Scallywag bunkers: geophysical investigations of WW2 Auxiliary Unit Operational Bases (OBs) in the UK. Issue 1 (2nd January 2020) - Carr, S.; Pringle, J.K.; Doyle, P.; Wisniewski, K.D.; Stimpson, I.G.
ABSTRACT: In 1940, with the fall of France imminent, Britain prepared secret 'Auxiliary Units' tasked with guerrilla activities [Scallywagging] in the invading army's rear. Patrols of four to eight highly skilled men used below-ground Operational Bases (OBs) in remote locations to avoid detection. No official records are released, but OBs were 'Mark I', enlarged deer setts, smuggler caves, etc., and Mark II, prefabricated designs by the Royal Engineers. This paper details three sites in Suffolk: one unknown Mark I was destroyed, a Mark II was partially intact and a Mark II was fully intact, all in secluded woods. Geophysical surveys found metal detectors optimal for location, with mid-frequency GPR/ERT optimal for characterisation. Archaeological finds included home-made braziers, 1940 kerosene heater stove, metal pans, ventilation systems and escape tunnels. This study shows OBs varied in construction and condition, with surveys detecting and characterising them, bringing WWII British 'invasion' history into the wider scientific community and public domain.